1978
DOI: 10.7164/antibiotics.31.1175
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo activity of piperacillin, a new broad-spectrum semisynthetic penicillin.

Abstract: Piperacillin sodium is a novel semisynthetic penicillin with broad spectrum activity against Gram-negative and-positive bacteria including anaerobes. In agar dilution tests with 522 clinical isolates, it inhibited at least 70-90% of each group of organisms at 16 meg/ml with the exception of the Serratia group which required 64 mcg/ml to inhibit 70 % of the isolates. Piperacillin was more potent than carbenicillin, ticarcillin and ampicillin against Klebsiella, Pseudomonas, Enterobacter and Serratia. Against Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…In vitro studies have shown the effectiveness of piperacillin against many pathogens including P. aeruginosa, E. coli, Klebsiella sp., other members of Enterobacteriaceae, and Bacteroides spp. (2,6,7,9). The results of the present study generally agree with these reports.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In vitro studies have shown the effectiveness of piperacillin against many pathogens including P. aeruginosa, E. coli, Klebsiella sp., other members of Enterobacteriaceae, and Bacteroides spp. (2,6,7,9). The results of the present study generally agree with these reports.…”
Section: Discussionsupporting
confidence: 83%
“…Piperacillin, a new semisynthetic penicillin with a broad spectrum of activity against both gram-positive and gram-negative pathogens (2)(3)(4)(5)(6)(7)(8)(9)(10), is currently undergoing clinical evaluations for efficacy and tolerability in a number of institutions. The present report summarizes the current results of one such investigation.…”
mentioning
confidence: 99%
“…It is particularly active against Pseudomonas aeruginosa, Klebsiella pneumoniae, and Streptococcus faecalis (3,(5)(6)(7)12).…”
mentioning
confidence: 99%
“…Studies Piperacillin is a new semisynthetic penicillin with in vitro activity significantly greater than that of either carbenicillin or ticarcillin (3, 5-7, 10, 12). It is particularly active against Pseudomonas aeruginosa, Klebsiella pneumoniae, and Streptococcus faecalis (3,(5)(6)(7)12 …”
mentioning
confidence: 99%
“…Piperacillin displays activity in vitro against a wide range of Gram-negative and Gram-positive bacteria as well as anaerobes (7,8,9,10,11,12,13). This group includes the clinically established carbenicillin and ticarcillin, and the newer acyl-ureidopenicillins, azlocillin, mezocillin, piperacillin and furazlocillin (Bay K 4999).…”
Section: Penicillinmentioning
confidence: 99%